A new type of excitation coil for measurement of liver iron overload by magnetic induction method - Ziyi Zhang; Peiguo Liu; Liang Ding; Liang Zhang (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
Noninvasive measurement of liver iron overload by magnetic induction (MI) method is a promising technique but low system sensitivity restricts its application due to weak secondary signal induced within biological tissues compared with the primary excitation signal. Based on the property of system sensitivity equation, a new type of excitation coil which can counteract the primary magnetic field itself at the receiving position is proposed in this paper. We derive an expression for z-component of magnetic field produced by the coil, and simulate the relation curve between the system sensitivity and the magnetic susceptibility of object. For comparison the relation curve when the excitation coil is circular coil is simulated as well. The results show that both the relation curves of the two types of excitation coil are well linear, while the system sensitivity can be more effectively improved by the new type of excitation coil than the circular coil.